Teacher Performance on Student Learning Outcomes - Muhamad Risman Pido; Melizubaida Mahmud; Sudirman Sudirman (State University of Gorontalo, 2023)
The purpose of this study was to determine the effect of teacher performance on student learning outcomes in integrated social studies subjects for class VIII at SMP Negeri 7 Telaga Biru, Gorontalo Regency. This study uses a quantitative approach, with survey research methods. The data used are primary data obtained from distributing questionnaires to Class VIII students at SMP Negeri 7 Telaga Biru, Gorontalo Regency. The number of sampling in this study amounted to 80 respondents. The data analysis technique used simple linear regression. The results showed that there was an influence of teacher performance on student learning outcomes in integrated social studies subjects for class VIII at SMP Negeri 7 Telaga Biru, Gorontalo Regency. The magnitude of the influence of teacher performance on student learning outcomes reached 48.8% while the remaining 51.2% was influenced by variables not examined.